2006
DOI: 10.1097/01.brs.0000216463.32136.7b
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Lumbar Spinal Stenosis

Abstract: Because of heterogeneity and overall poor quality, no firm conclusions about the diagnostic performance of the different tests can be drawn. Better-designed studies exploring the accuracy of diagnostic tests are needed to improve the diagnostic policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(31 citation statements)
references
References 34 publications
(52 reference statements)
1
29
0
1
Order By: Relevance
“…The patients were all individually assessed and the chosen surgery was regarded as optimal for each patient [25, 26]. The intention was to release the pressure on nerve tissue by removing enough of the bone, facet joints and ligaments due to the compression.…”
Section: Methodsmentioning
confidence: 99%
“…The patients were all individually assessed and the chosen surgery was regarded as optimal for each patient [25, 26]. The intention was to release the pressure on nerve tissue by removing enough of the bone, facet joints and ligaments due to the compression.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, it makes sense to establish a Torg ratio for the lumbar spine that takes into account the AP diameter of the lumbar spinal canal and the AP diameter of the lumbar vertebral body. De Graaf et al [17] suggested that radiological studies have inherent inaccuracies, and this has been shown to be true by a number of radiological studies with conflicting conclusions [11, 12, 3032]. Thus, a morphoanatomical study to establish a definite Torg ratio criterion for lumbar stenosis is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature suggests that various estimates of the sensitivity and specificity of radiographic diagnosis of lumbar stenosis should be considered inaccurate due to the lack of an independent reference standard [1117]. Exact measurements that define this condition are needed, as are simple parameters that will accurately predict if LSS is present.…”
Section: Introductionmentioning
confidence: 99%
“…Neurogenic claudication is defined as radiculopathy or pain and weakness in one or both lower extremities that worsen with walking and may be relieved with sitting or bending forward. [2627] MRI without gadolinium is considered the best imaging modality for diagnosing spinal stenosis. [272829] Specific measurements of spinal canal size on radiological imaging have not been shown to correlate with clinical symptoms of spinal canal stenosis.…”
Section: Lumbar Spinal Stenosismentioning
confidence: 99%
“…[2627] MRI without gadolinium is considered the best imaging modality for diagnosing spinal stenosis. [272829] Specific measurements of spinal canal size on radiological imaging have not been shown to correlate with clinical symptoms of spinal canal stenosis. However, a cross-sectional area of the dural sac of <110 mm 2 on MRI with can be useful in decision making for patients with clinically suspected lumbar stenosis.…”
Section: Lumbar Spinal Stenosismentioning
confidence: 99%